Draft Annual Plan 2006-2007 (Statements) Government of Tripura - Planning Commission (Planning Commission, 2006)
Sub-Sector wise proposed outlays Draft Annual Plan 2006-07 Proposed Outlays Major/Minor Head wise Draft Annual Plan 2006-07-proposed outlays Physical Targets and Achievements Statement Regarding Externally Aided Projects Bharat Nirman Programmes Draft Annual Plan 2006-07- Outlay by Heads of Developments for District Plan Centrally Sponsored Schemes Draft Annual Plan 2006-07- Financial Outlays for TSP Draft Annual Plan 2006-07- Physical Target for TSP Annual Plan 2006-07 Financial Outlays/Expenditure for Voluntary Sector.
Planning (P and C) Department, Government of Tripura